LEST WE MISS IT: ANXIETY AND DEPRESSION SYMPTOMS IN ADULT PATIENTS WITH GENERALIZED TONIC CLONIC SEIZURES IN PAKISTAN - Ahmad, Sabih; Hussain, Sadiq; Tayyeba Kiran, Tayyeba; Naz, Anum (Journal of Postgraduate Medical Institute, 2021)
Objective: To find out the frequency of and compare anxiety and depression in epileptic and non-epileptic matched individuals. Methodology: This cross sectional study was carried out at a tertiary care hospital in Pakistan including 200 epilepsy patients, visiting the department of medicine and psychiatry for follow-up. The second group consisted of 200 epilepsy free healthy matched individuals. Hospital anxiety and depression scale (HADS) was administered to assess participants’ anxiety and depression. Means, frequencies, and Chi-square were applied to analyze the collected data. Results: Epilepsy patients were more likely to have depression (x2 = 33.56, p<.001) and anxiety (x2 = 55.96, p<.001) as compared to the control group. Anxiety symptoms were found in 42%, while depression in 34% of the patients. This was further distributed into mild, moderate and severe symptoms. Being unmarried, belonging to a particular age group, full time employment and a lower educational level were related with the anxiety symptoms while particular age group, lower educational level and full time employment with symptoms of depression. Conclusion: The Generalized Tonic and Colonic Seizures (GTCS) epilepsy population has a significantly higher rate of comorbid anxiety and depression symptomatology.